The globalisation of technology: a new taxonomy - Archibugi, D; Michie, J (Oxford University Press, 1995)
Much has been written on the increasingly international generation, transmission and diffusion of technologies, with the phenomenon having been given its own term—techno-globalism—and interpreted by some as displacing national systems of innovation and making redundant and futile any attempt by national governments to foster technological development domestically. This paper reconsiders the evidence by developing a new taxonomy and investigating separately: (a) the global exploitation of technology, (b) global technological collaboration and (c) the global generation of technology. We find quite distinct answers when the degree of globalisation is evaluated separately on these three definitions.